Quality Assurance in Higer Education and the Link to Internationalisation. - Wende, Marijk van der (2011)
Quality and internationalisation: a problem definition Internationalisation of higher education seems to be strongly related to the aim to improve the quality of higher education. The idea that internationalisation should not be seen as an end in itself but as a means for quality enhancement has been the basis of many policy documents. In the 1980s publications of the OECD presented the quality perspective in particular in relation to the expected qualitative impact of the presence of foreign students on the teaching and learning process and on the institution’s curriculum and services (Ebuchi, 1989). In the Maastricht Treaty (1992) the articles which provide the basis for Community action in higher education reflect the aim of improving the quality of education through co-operation between the member states of the European Union. Also national policies for internationalisation of higher education generally display the quality objective (Kalvermark & Van der Wende, 1997) and so do many institutional policy documents on internationalisation.